Kedudukan Hukum Khusus dalam Pengujian Undang-Undang di Mahkamah Konstitusi - Fitra Arsil; Qurrata Ayuni (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
In general, the Constitutional Court has the view that political parties that have seats in the DPR and/or members of the DPR already have legislative space and do not have the legal standing to review laws. However, there are a number of exceptions in many cases where political parties and members of the DPR are considered to have a special position even though they are also discussing the passed laws. This paper discusses the jurisprudential pattern of the Constitutional Court in granting special legal status to political parties and members of the DPR. Using the case approach method in collaboration with the comparison method this paper seeks to map the potential for testing with specific constitutional rights. The findings in this paper reinforce the concept that although the results of law formation in the legislature and legal review in the judiciary are equally binding for citizens, the process of law formation and legal review has a different character and these differences are beneficial within the framework of checks and balances.